Impact Of The Intervention Of World Bank-Sponsored State Education Sector Project On Teachers’ Job Performance And Students’ Performance Outcome In Kano State: The Journey So Far. - Ibrahim, Asiya Aliyu (International Journal of Advanced Science and Technology, 2020)
The research work is about finding the impact of the World Bank-sponsored State Education Sector (TPD) Project on teachers’ job performance and students’ academic performance in Kano state. For this study, an ex-post factor research design was used. The population for the study comprised all the teachers in primary schools in the six selected LGAs (3-SESP and 3-non SESP) and their students, who altogether totaled 579,568. Using multi-stage cluster sampling and a simple random sampling technique, a sample of 360 teachers and 384 students were drawn.  A researcher- made teacher performance evaluation questionnaire (TPEQ) was developed and administered by the head teachers. Others were lesson observation for 360 sampled teachers in lower basics and Students General Performance Tests on Mathematics, English and Basic Science (SGPTOMEBS) conducted by the researcher and 3 research assistants. Content/face validation for the instruments were established and the instruments found to be reliable with Cronbach’s alpha values of .931, and .753 respectively. Data was analyzed using standard deviation, mean point value, percentages and t-test of significance. The result from the study indicated that though there was a slight rise in teachers’ professional development in the SESP LGAs, their performances, and those of their students are still questionable, as the SESP TPD has not been seen to significantly improve both teacher and student performances. The work recommends that for teachers’ performance to increase significantly resulting from the Teacher Professional Development training received, several measures have to be taken, especially in our existing situation when the quality of education is no longer appreciable. This includes rigorous enlightenment campaigns to re-educate teachers on the significance of utilizing and maintaining acquired knowledge for personal development and for improvement of basic education in Kano state.